Democratic Parenting in Terms of The Self-Concept of Tionghua Students - Salim, Jennifer Creszentia; Hartati, Merry; Yuliana, Yuliana; Tandera, Ruben Luis; Hartini, Sri; Tarigan, Eltalina (Psikostudia : Jurnal Psikologi, 2023)
Today, many children are not only required to learn formal education but also have to learn non-formal education. One of them is to have a good character. Parenting plays an important role in the formation of children's character. From an early age, children will be introduced to how to behave well, good communication, and so on. The character of the child will have a great influence in the future for the survival of the child. Democratic parenting is a series of parental actions in interacting with adolescents that apply a parenting style that encourages adolescents to be independent but still provides boundaries and control over adolescent actions, provides opportunities for dialogue, is warm and nurturing and shows pleasure and support in response to adolescent constructive behavior. The purpose of this study is to test and prove the relationship between democratic parenting in terms of self-concept. The research sample consisted of 115 students of Sultan Iskandar grade 1 high school. Young through Purposive Sampling Technique. The research data were collected using a democratic parenting scale consisting of 19 items and a self-concept scale consisting of 21 items." The data were analyzed using the Pearson Product Moment correlation method. Research results. Shows that democratic parenting has a positive and significant effect in terms of self-concept with a correlation coefficient of attain. 0.320 and a significance value of 0.001 (p < 0.05) which means that the higher the democratic parenting style, the higher the self-concept and vice versa.Pada zaman sekarang, banyak anak-anak bukan hanya dituntut untuk belajar pendidikan formal saja tetapi juga harus belajar pendidikan non formal. Salah satunya adalah memiliki karakter yang baik. Pola Asuh orang tua sangat berperan penting dalam pembentukan karakter anak. Sejak dini, anak-anak akan diperkenalkan bagaimana cara berperilaku yang baik, komunikasi yang baik, dan sebagainya. Karakter anak akan memiliki pengaruh yang besar di masa depan untuk kelangsungan hidup sang anak. Pola asuh demokratis adalah serangkaian tindakan orang tua dalam berinteraksi dengan remaja yang menerapkan gaya pengasuhan orang tua yang mendorong remaja untuk mandiri namun tetap memberikan batasan dan kendali atas tindakan-tindakan remaja, memberikan kesempatan untuk berdialog, bersifat hangat dan mengasuh serta memperlihatkan rasa senang dan dukungan sebagai respons terhadap tingkah laku konstruktif remaja. Tujuan daripada dilakukannya penelitian ini adalah untuk menguji dan membuktikan hubungan antara pola asuh demokratis ditinjau dari konsep diri. Sampel penelitian terdiri dari 115 siswa-siswi SMA kelas 1 Sultan Iskandar. Muda melalui Teknik” Purposive Sampling. Data penelitian dikumpul menggunakan skala pola asuh demokratis yang terdiri dari 19 item dan skala konsep diri terdiri dari 21 item.” Data dianalisis dengan menggunakan metode korelasi Pearson Product Moment. Hasil penelitian. Menunjukkan bahwa pola asuh demokratis berpengaruh positif dan signifikan ditinjau dari’ konsep diri dengan koefisien korelasi sebesar. 0.320 dan nilai signifikansi sebesar 0.001 (p < 0.05) yang berarti semakin tinggi pola asuh demokratis maka akan semakin, tinggi konsep diri dan berlaku pula sebaliknya.